2020
DOI: 10.1088/1674-4926/41/11/111406
|View full text |Cite
|
Sign up to set email alerts
|

A survey of active quasi-circulators

Abstract: With the development of multi-band wireless communication and the increasing data transmission rate, the circulator as an antenna interface must be able to work in multiple frequency bands and provides large bandwidth. It presents a high challenge to the design of circulators, especially the active quasi-circulators. In this survey, we review the representative active quasi-circulators and summarize three different techniques and the corresponding structures to show an incremental improvement of the isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In Figure 2, difference between active 3‐way and active‐quasi circulator is shown 13 . From the illustration, it can be observed that an active‐quasi circulator has similar operation principle compared to the conventional three‐way circulator.…”
Section: Theory and Principle Of Operationmentioning
confidence: 97%
See 4 more Smart Citations
“…In Figure 2, difference between active 3‐way and active‐quasi circulator is shown 13 . From the illustration, it can be observed that an active‐quasi circulator has similar operation principle compared to the conventional three‐way circulator.…”
Section: Theory and Principle Of Operationmentioning
confidence: 97%
“…In Figure 2, difference between active 3-way and active-quasi circulator is shown. 13 From the illustration, it can be observed that an active-quasi circulator has similar operation principle compared to the conventional three-way circulator. However, quasi-circulator does not allow signal transmission from port 3 (receiver) to port 1 (transmitter), due to which the S parameter S 13 = 0.…”
Section: Theorymentioning
confidence: 98%
See 3 more Smart Citations